If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 5 = 25 + -1y Reorder the terms: 5 + 3y = 25 + -1y Solving 5 + 3y = 25 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 5 + 3y + y = 25 + -1y + y Combine like terms: 3y + y = 4y 5 + 4y = 25 + -1y + y Combine like terms: -1y + y = 0 5 + 4y = 25 + 0 5 + 4y = 25 Add '-5' to each side of the equation. 5 + -5 + 4y = 25 + -5 Combine like terms: 5 + -5 = 0 0 + 4y = 25 + -5 4y = 25 + -5 Combine like terms: 25 + -5 = 20 4y = 20 Divide each side by '4'. y = 5 Simplifying y = 5
| -5(z+8)-(-8z-3)=2z | | 243-61m=882 | | 3x+7=17-6x | | x+14=5x+30 | | 18x+54y+110z=500 | | -15x=-45 | | a=yn+y | | 4-3x=-2x-1 | | 4(x+2)-2(x-4)=16+2(x-6) | | 3(x-6)=-12+3(x-2) | | mp+mv=t | | (2x+1)(x+9)=9 | | -9x+7=4x+1 | | 3(x+2)-6=24 | | 5+8x=3x+15 | | 50x^2+20x-16=0 | | 6+0.10x=.15x+8 | | 9x-6y=30 | | -(3x-5)-(2x-6)+1=-5(x-1)-(3x+2)+3 | | 8x(7-24)=32 | | 8x(7-24)= | | -2p+120=3p+20 | | 0.5+0.05x=9.8 | | (x-3)(x^2+3x+9)=98 | | 0.5+0.05x=9.6 | | 3x=x+45 | | -14579x-63903= | | 1363x-15942x= | | -35x+1398x= | | 15942x+63903= | | 3d*5e= | | -35x+1373-15995+63210= |